Prediction of coal ash fusibility based on metal ionic potential concentration. (October 2021) - Xiao, Huixia; Wang, Yifei; Li, Jilin; Bao, Zebin; Mu, Liying; Yu, Guangsuo
Abstract: To investigate the quantitative relationship between ionic potential and coal ash fusibility, the chemical compositions and ash fusion temperatures (AFTs) of 214 coal ashes were tested. The prediction models of AFTs with the metal ionic potential concentration ( C M P = ∑ w i ∗ z i M i ∗ r i ∑ w i / M i ) were established by linear fitting. The mineral evolution under different CMP was calculated by FactSage 7.2. and was used to reveal the effect mechanism of CMP on AFTs. The results showed that AFTs initially emerged a negative correlation (24.13 nm −1 MP <36.97 nm −1 ) followed by a positive correlation (36.97 nm −1 MP <52.26 nm −1 ). Their correlation coefficients ranged from 0.8 to 0.95, emerging a trend of DT < ST < HT < FT, and the model may be more accurate for positive correlation curve due to the partial volatilization of alkali metals in the negative correlation curve. CMP was divided into the basic oxide monomer skeleton region (24.13 nm −1 MP <30.00 nm −1, high AFTs), the silicoaluminate low-temperature eutectic region (30.00 nm −1 MP <40.00 nm −1., low AFTs), the quartz skeleton region (40.00 nm −1 MP <50.00 nm −1, high AFTs) and the mullite skeleton region (50.00 nm −1 MP <52.26 nm −1, high AFTs) according to the difference of mineral skeleton. Highlights: The metal potential concentration (CMP ) was defined and calculated. The prediction model of AFTs with CMP was established. The mineral evolution under different CMP was used to reveal the effect mechanism of CMP on AFTs.